Approximations between the legal-ecological views of brazilian environmental constitutionalism and eastern awareness - Bellincanta de Souza, Filipe (International Journal of Environmental Resilience Research and Science, 2025)
This work aims to show the need of conscience to reach a better interaction in the Society, specifically, crossing the Eastern awareness of Ying-Yang. In this article was used the indutive method through bibliographic analysis. It was developed to demonstrate how the Environmental Constitutionalism in Brazil recognizes through approximations between the legal-ecological and the Eastern awareness. Going further, to fully and securely guarantee to avoid threats from environmental, social, economic, political, human and emotional risks, the transition to sustainability through the spread of balanced awareness from the Yin-Yang perspective offers a more assertive way forward, rather than a static confrontation between modus vivendi and modus operandi of peoples.